Are Shorter Cumulative Temporary Contracts Worse Stepping Stones? Evidence from a Quasi-Natural Experiment - Jan Kabátek; Ying Liang; Kun Zheng (Institute of Labor Economics (IZA), 2022)
Temporary employment contracts are often regarded as 'stepping stones' for workers' careers, because they can help inexperienced workers secure a permanent contract. Our study evaluates whether this stepping-stone function is moderated by the contract duration, exploiting a Dutch policy reform that shortened the maximum duration of sequences of temporary contracts with the same employers from 3 years to 2 years. Leveraging a sharp regression discontinuity design and administrative register data, we show that the reform accelerated the transitions of temporary workers to permanent contracts with the same employers, with the effect being strongest among those working for the same employers for 1-2 years. We conclude that the reform brought more job security to temporary workers without impeding the stepping-stone function of their contracts.
Keywords: J28; J41; J42; 330; temporary contracts; permanent contract; stepping stone; chain rule